MENGGAGAS AMANDEMEN UUD 1945 DARI PEMILUKADA - Melfa, Wendy (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The Head of Region Election is a means of democracy for the autonomy region in the efforts to implement the local autonomy through the process of decentralization in the political field to manage and take care the government’s matters in the efforts to improve the people’s welfare which is based on the Section 18 Article (4) Basic Constitution 1945 of Republic Indonesia as its constitutional foundation. At the operational level of constitutional base can cause multiple interpretations about the democracy model that can be carried out. Therefore, that decision needs to be taken an amendment so that it results the clarity and firmness of the Head of Region Election stated firmly and elected directly by people. Furthermore, there’s still “debatable” opinion to classify whether head of general election is included in the regional government regime or the public election regime, so that it needs an amendment towards Chapter VIIB about General Election Section 22E Article (2) Basic Constitution 1945 of Republic Indonesia, that’s why to classify the Head of Region into the General Election management together with House of Representative (DPR), Board of Regional Representative (DPD) President and Vice President and also Regional House of Representative (DPRD). This case will clarify that Head of Region Election is categorized or classified in the General Election regime.Key words: local autonomy, head of region election, amendment